Radiation Shielding And Optical Properties Of Added Bao And Wo3 To Bi2o3-Zno-B2o3-Sls Glass Network At Selective Photon Energy - Khazaalah, Thair Hussein Abedalrahman (2023)
In the current study, WO3 and BaO were added to Bi2O3-ZnO-B2O3-SLS glass to develop leadbrown. Furthermore, the Soda-Lime-Silica (SLS) glass waste used to limit the accumulation glass waste, which requires extensive time to decompose. This also saves on the consumption of pure SiO2, which is a finite resource. The meltquenching method was utilized to fabricate eleven glass samples. The structural, physical, optical, and attenuation characteristics were studied for current glass samples. The XRF results showed that SLS waste glass contained multi-chemical compounds such as 74.1% SiO2 and other minor elements.